Efficacy and safety of chemoradiotherapy plus immune checkpoint inhibitors for the treatment of locally advanced cervical cancer: a systematic review and meta-analysis - Zhao, Zhihong; Ruan, Jian; Fang, Minjie; Liu, Jingwen; Liao, Guixiang (Frontiers in Immunology, 2024)
Background: Radiotherapy plus concurrent chemotherapy is a standard method for treating locally advanced cervical cancer (LACC). Immune checkpoint inhibitors (ICIs) are widely applied in the treatment of recurrent cervical cancer, metastatic cervical cancer or LACC. The efficacy and safety of radiotherapy plus immunotherapy for LACC require further investigation. The objective of this review and meta-analysis was to analyze the efficacy and safety of concurrent chemoradiotherapy (CCRT) combined with ICIs for treating LACC on the basis of the results of randomized controlled trials (RCTs). Methods: We comprehensively searched electronic databases to identify RCTs that focused on CCRT plus ICIs for LACC treatment. The outcomes included the objective response rate (ORR) and progression-free survival (PFS), overall survival (OS) and adverse events (AEs). A standard method for systematic review and meta-analysis was used. Review Manager 5.4 was used for data combination and analyses. Results: Three RCTs involving 1882 participants with LACC were identified and included in the systematic review and meta-analysis. CCRT plus ICIs improved the rates of PFS (hazard ratio [HR]: 0.76, 95% confidence interval [CI]: CI: 0.64, 0.91, P = 0.002) and OS (HR: 0.7695% CI (95% CI 0.58–0.99, P = 0.04) in patients with LACC. Compared with the control group, the CCRT plus immunotherapy group had an increased ORR (OR: 1.37, 95% CI: 1.02,1.85, P=0.04). The two methods had similar rates (HR=1.99, 95% CI: 0.99, 1.43; P=0.07) of treatment-related grade 3 or higher AEs. The CCRT plus immunotherapy group had a higher rate than did the control group (HR: 2.68, 95% CI: 1.38, 5.21; P=0.004) in terms of any grade immunotherapy-related AEs. Conclusions: CCRT plus ICIs is efficacious and safe for the management of LACC. The addition of ICIs to CCRT improved the rates of PFS and OS in patients with LACC. The adverse effects of immunotherapy-related AEs should be strictly examined and managed in a timely manner.